Beyond capital fundamentalism: Harrod, Domar and the history of development economics - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2015)
The origins of "capital fundamentalism' – the notion that physical capital accumulation is the primary determinant of economic growth – have been often ascribed to H arrod's and Domar's proposition that the rate of growth is the product of the saving rate and of the outpu t - capital ratio. I t is argued here that development planners in the 1950s reinterpreted and adapted the growth formula to their agenda in order to calculate "capital requirements". Development economists at the time (Lewis, Hirschman, Rostow and others) were aware that Harrod's and Domar's growth models addressed economic instability based on Keynesian multiplier analysis, which diff ered from their concern with long - run growth in developing economies. Harrod eventual ly applied his concept of the natural gro wth rate to economic development . He claimed that the growth of developing economies was determined by their ability to implement technical progress – not by capital accumulation, subject to diminishing returns. Dom ar pointed out that the increm ental capital - output ratio was more likely a passive result of the interaction between the propensity to save and technological progress, instead of a causal factor in the determination of growth.
Keywords: B22; B31; O10; 330; Capital fundament alism; Harrod; Domar; development economics; saving